The impossibility of historical change in the thought of Louis Althusser : a critical comparison of the epistemologies and social theories of Louis Althusser and Jurgen Habermas - Van Breda, John(John Reitz) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1985.